International Journal of Impact Engineering - International Journal of Impact Engineering (Elsevier, 2026)
The International Journal of Impact Engineering, established in 1983 publishes original research findings related to the response of structures, components and materials subjected to impact, blast and high-rate loading. Areas relevant to the journal encompass the following general topics and those associated with them: Behaviour and failure of structures and materials under impact and blast loading; Systems for protection and absorption of impact and blast loading; Terminal ballistics; Dynamic behaviour and failure of materials including plasticity and fracture; Stress waves; Structural crashworthiness; High-rate mechanical and forming processes; Impact, blast and high-rate loading/measurement techniques and their applications.
FI 1.3
Q1
Keywords: Physical Sciences & Engineering; Energy & Environmental Impact; Acuerdos transformativos; Transformative agreements; Ingeniería de impacto; Mecánica de materiales; Cargas dinámicas; Ondas de choque